Serum Levels of Myonectin Are Lower in Adults with Metabolic Syndrome and Are Negatively Correlated with Android Fat Mass (2023)
ABSTRACT:Myonectin has shown beneficial effects on lipid regulation in murine models; therefore, it may have implications in the pathophysiology of metabolic syndrome (MS). We evaluated the relationship between serum myonectin and serum lipids, global and regional fat mass, intramuscular lipid content, and insulin resistance (IR) in adults with metabolic risk factors. This was a cross-sectional study in sedentary adults who were diagnosed with MS or without MS (NMS). Serum myonectin was quantified by enzyme-linked immunosorbent assay, lipid profile by conventional techniques, and free fatty acids (FFA) by gas chromatography. Body composition was assessed by dual-energy X-ray absorptiometry and intramuscular lipid content through proton nuclear magnetic resonance spectroscopy in the right vastus lateralis muscle. IR was estimated with the homeostatic model assessment (HOMA-IR). The MS (n = 61) and NMS (n = 29) groups were comparable in age (median (interquartile range): 51.0 (46.0-56.0) vs. 53.0 (45.5-57.5) years, p > 0.05) and sex (70.5% men vs. 72.4% women). MS subjects had lower serum levels of myonectin than NMS subjects (1.08 (0.87-1.35) vs. 1.09 (0.93-4.05) ng·mL-1, p < 0.05). Multiple linear regression models adjusted for age, sex, fat mass index and lean mass index showed that serum myonectin was negatively correlated with the android/gynoid fat mass ratio (R2 = 0.48, p < 0.01), but not with the lipid profile, FFA, intramuscular lipid content or HOMA-IR. In conclusion, serum myonectin is lower in subjects with MS. Myonectin negatively correlates with a component relevant to the pathophysiology of MS, such as the android/gynoid fat mass ratio, but not with other components such as FFA, intramuscular fat or IR.